2022
DOI: 10.1007/s00170-022-08754-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrolyte flushing and surface state on electropolishing TB2 titanium alloy

Abstract: TB2 titanium alloys are widely used in the aerospace industry. A high surface quality is required for the performance and fatigue life of titanium alloy parts. Electropolishing is useful for thin metal plates owing to its good processability and conformability. In this study, electrolyte ushing was proposed for electropolishing a large surface and a NaCl-containing ethylene glycol electrolyte was adopted. Three different mechanical grindings were employed for pretreatment, and the ideal surface quality was obt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(25 reference statements)
2
0
0
Order By: Relevance
“…It is also noted that the surface quality of the brass was improved due to rapid decrease of roughness at the initial phase of polishing. A similar trend was also reported in the work of Wei et al [30].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It is also noted that the surface quality of the brass was improved due to rapid decrease of roughness at the initial phase of polishing. A similar trend was also reported in the work of Wei et al [30].…”
Section: Resultssupporting
confidence: 90%
“…In a study conducted by Yang et al [29], it was observed that this technique could yield a non-uniform surface roughness. Similar findings were also observed in the study of Wei et al [30]. Yang et al [31] also developed a mechanism that allowed controlling the inlet and outlet of the electrolyte bath of the EP unit.…”
Section: Fig 2 Diffusion Layer On the Electropolished Surfacesupporting
confidence: 82%